A p-dichlorophenyl polyphenylene sulfide and a method for preparing the same

CN122978441APending Publication Date: 2026-10-27JIANGSU HUAI JIANG TECH CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202611491851.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-09-23
Publication Date
2026-10-27

AI Technical Summary

Technical Problem

上述方案有助于获得聚苯硫醚树脂,但多侧重主链增长或工艺效率,对引入聚醚砜低聚物链段后的共价连接、界面调节、结晶规整性、残留氯降低和加工流动性之间的协同平衡关注不足,仍难同时满足结构完整与耐热加工需求

Benefits of technology

[0052]1.通过在聚苯硫醚主链段中引入由羟基封端聚醚砜低聚物形成的聚醚砜低聚物链段,并使两类链段通过芳醚键共价连接,可减少单纯物理共混导致的链段迁移和界面分离倾向,提高聚醚砜低聚物链段在规定N-甲基吡咯烷酮萃取条件下的保留稳定性,并改善最终产物粉体的组分分布均一性。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122978441A_ABST
    Figure CN122978441A_ABST
Patent Text Reader

Abstract

The application belongs to the field of high-performance polymer materials, and provides a p-dichlorophenyl polyphenylene sulfide and a preparation method thereof. The method first forms a p-chlorophenyl end group polyphenylene sulfide prepolymer, and then introduces a hydroxyl-terminated polyether sulfone oligomer activated by anhydrous potassium carbonate, so that the polyphenylene sulfide main chain segment and the polyether sulfone oligomer segment are covalently connected through an aryl ether bond. In the segment connection step, the total of the dry basis mass of the p-chlorophenyl end group polyphenylene sulfide prepolymer and the hydroxyl-terminated polyether sulfone oligomer is 100 wt%, the dry basis mass ratio of the p-chlorophenyl end group polyphenylene sulfide prepolymer is 88.00-98.00 wt%, and the dry basis mass ratio of the hydroxyl-terminated polyether sulfone oligomer is 2.00-12.00 wt%. The obtained material is used for the forming and processing of heat-resistant engineering plastics.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of high-performance polymer materials, specifically to a p-dichlorophenyl polyphenyl sulfide and its preparation method. Background Technology

[0002] Polyphenylene sulfide (PPS) possesses high heat resistance, chemical resistance, dimensional stability, and electrical insulation, making it valuable in fields such as electronics, automotive parts, corrosion-resistant pipes, precision structural components, and high-temperature filtration materials. As engineering plastics evolve towards lightweight, long-term heat resistance, low ionic residue, and high-precision molding, materials not only need to maintain the original crystallinity regularity and heat distortion stability of PPS segments, but also require a wider process window in melt processing, interface modification, end-group control, and post-processing purification. Insufficient structural integrity can lead to segment migration, interface weakening, or thermal history sensitivity during subsequent molding and service. Conversely, solely pursuing high crystallinity and high heat resistance may result in decreased processing fluidity, insufficient space for segment modification, and difficulty in controlling residual end-groups. Therefore, constructing a PPS modification system that balances crystallinity and heat resistance, structural integrity, low residue, and processability has become a key direction in the development of high-performance polymer materials.

[0003] Existing publicly available technologies mainly focus on the polycondensation of sodium sulfide and p-dichlorobenzene in polar aprotic solvents to prepare polyphenylene sulfide (PPS). These technologies utilize desalting, dehydration, salting aids, or post-treatment methods to improve molecular weight, color, yield, and residual ion levels. For example, Chinese patent application CN103275320A discloses a method for preparing linear high-molecular-weight PPS using sodium sulfide and p-dichlorobenzene as main raw materials under N-methylpyrrolidone and lithium chloride conditions. CN107254047B discloses a method for preparing PPS through the polycondensation of p-dichlorobenzene, involving treatment routes such as sodium sulfide nonahydrate, N-methylpyrrolidone, and azeotropic dehydration. While these methods contribute to obtaining PPS resin, they primarily emphasize main chain growth or process efficiency, paying insufficient attention to the synergistic balance between covalent bonding, interface regulation, crystal regularity, residual chlorine reduction, and processing fluidity after the introduction of polyethersulfone oligomer segments. Consequently, it remains difficult to simultaneously meet the requirements of structural integrity and heat-resistant processing. Summary of the Invention

[0004] The purpose of this invention is to provide a p-dichlorophenyl polyphenylene sulfide and its preparation method, which solves the current problem that it is difficult to simultaneously achieve chain segment stability, crystal heat resistance, low residual chlorine and processing fluidity.

[0005] This invention maintains the crystallinity and heat resistance of the polyphenylene sulfide (PPS) main chain segment and allows the PPS oligomer segments introduced by the hydroxyl-terminated PPS oligomer to participate in chain segment linkage via aryl ether bonds. By utilizing proportion matching, end-group reactions, and post-treatment control, the interference of chain segment introduction on crystallinity regularity is reduced, while simultaneously minimizing the impact of residual terminal chlorine on processing stability. This achieves a synergistic balance between the stability and heat-resistant processing performance of the modified chain segments. In this specification, the ratio of PPS main chain segment to PPS oligomer segments is calculated based on the dry weight of the p-chlorophenyl-terminated PPS prepolymer and the hydroxyl-terminated PPS oligomer in the chain segment linkage step; the sum of their dry weights is 100 wt%. The segment retention rate after N-methylpyrrolidone extraction is an independent indicator obtained by accelerated extraction evaluation after separate sampling of the final product and is not used to correct the aforementioned dry weight ratio. The segment retention rate after extraction reflects the mass retention state of polyethersulfone oligomer segments under specified extraction conditions and is not used to calculate the actual grafting amount or the number of aromatic ether bonds. Unless otherwise stated, the solid content of the polyethersulfone potassium salt activation solution refers to the proportion of the dry basis mass of the hydroxyl-terminated polyethersulfone oligomer to the total mass of the activation solution, excluding the added anhydrous potassium carbonate; undissolved matter refers to the proportion of the solid mass retained when the activation solution is filtered through a 100μm metal filter to the total mass of the activation solution before filtration. The segment stability refers to the retention state of the polyethersulfone oligomer segments under specified extraction conditions and the retention state of the final product powder morphology, excluding evaluations of mechanical properties such as tensile, bending, and impact.

[0006] To achieve the above objectives, the present invention provides the following technical solution:

[0007] A p-dichlorophenyl polyphenylene sulfide, said p-dichlorophenyl polyphenylene sulfide comprising:

[0008] The polyphenylene sulfide backbone segment formed by the condensation polymerization of p-dichlorobenzene and sodium sulfide nonahydrate and present in the final product; and

[0009] The polyethersulfone oligomer segment introduced into and present in the final product is a hydroxyl-terminated polyethersulfone oligomer formed by the polycondensation of 4,4'-dihydroxydiphenyl sulfone and 4,4'-dichlorodiphenyl sulfone.

[0010] Wherein, the covalent bond between the polyphenylene sulfide main chain segment and the polyethersulfone oligomer chain segment is an aryl ether bond. In the chain linking step of preparing the p-dichlorophenyl polyphenylene sulfide, based on the sum of the dry basis mass of the p-chlorophenyl-terminated polyphenylene sulfide prepolymer used to form the polyphenylene sulfide main chain segment and the hydroxyl-terminated polyethersulfone oligomer used to form the polyethersulfone oligomer chain segment being 100wt%, the dry basis mass of the p-chlorophenyl-terminated polyphenylene sulfide prepolymer is 88.00-98.00wt%, the dry basis mass of the hydroxyl-terminated polyethersulfone oligomer is 2.00-12.00wt%, and the sum of the two is 100wt%.

[0011] Furthermore, the total chlorine content of the p-dichlorophenyl polyphenylene sulfide is 200-1500 mg / kg, the ash content is 0.005-0.150 wt%, and the weight-average molecular weight is 2.0 × 10⁻⁶. 4 -8.0×10 4 g / mol. The total chlorine content is the total chlorine content of the final dried product as determined by combustion ion chromatography, including covalent chlorine corresponding to terminal chlorine groups and extractable free chlorine; the value of the terminal chlorine group content converted to chlorine mass is not greater than the total chlorine content.

[0012] Furthermore, the residual N-methylpyrrolidone content of the p-dichlorophenyl polyphenyl sulfide is 20-1000 mg / kg.

[0013] Furthermore, the polyethersulfone oligomer segments are introduced by hydroxyl-terminated polyethersulfone oligomers, which are prepared through the following steps:

[0014] A1. Add 4,4'-dihydroxydiphenyl sulfone, 4,4'-dichlorodiphenyl sulfone, anhydrous potassium carbonate, N-methylpyrrolidone, and toluene to a reaction vessel equipped with a stirrer, condenser, and water separator, wherein the molar ratio of 4,4'-dihydroxydiphenyl sulfone to 4,4'-dichlorodiphenyl sulfone is 1.04-1.20:1, and the molar ratio of anhydrous potassium carbonate to 4,4'-dihydroxydiphenyl sulfone is 1.05-1.40:1;

[0015] A2. Under industrial-grade nitrogen protection, reflux azeotropic dehydration at 140-165℃ for 1.0-3.0h;

[0016] A3. Heat to 170-190℃ for condensation for 2.0-6.0 h to obtain a reaction solution containing hydroxyl-terminated polyethersulfone oligomers;

[0017] A4. The reaction solution containing the hydroxyl-terminated polyethersulfone oligomer is subjected to precipitation, washing, filtration and drying to obtain the hydroxyl-terminated polyethersulfone oligomer;

[0018] The hydroxyl-terminated polyethersulfone oligomer has a number-average molecular weight of 1400-7500 g / mol, a hydroxyl value of 15-80 mg KOH / g, a terminal hydroxyl content of 0.27-1.43 mmol / g, and a residual potassium ion content of 20-1000 mg / kg.

[0019] Furthermore, the polyphenylene sulfide backbone segment is introduced from a p-chlorophenyl-terminated polyphenylene sulfide prepolymer, which is prepared through the following steps:

[0020] B1. In a closed, pressure-resistant reactor equipped with a condenser and water separation unit and under industrial-grade nitrogen protection, sodium sulfide nonahydrate, N-methylpyrrolidone, anhydrous lithium chloride, and anhydrous sodium acetate are added to the reactor, and the temperature is raised to 160-205℃ for dehydration for 1.0-4.0 hours.

[0021] B2. Add p-dichlorobenzene, wherein the molar ratio of p-dichlorobenzene to sodium sulfide (calculated as anhydrous sodium sulfide) is 1.005-1.050:1;

[0022] B3. Prepolymerize at 220-245℃ and under system autogenous pressure for 0.5-2.0h, then polymerize at 250-275℃ and under system autogenous pressure for 1.0-4.0h. After solid-liquid separation, washing and drying, the p-chlorophenyl-terminated polyphenylene sulfide prepolymer is obtained.

[0023] The p-chlorophenyl-terminated polyphenylene sulfide prepolymer has a terminal chlorine group content of 0.020-0.180 mmol / g and a weight-average molecular weight of 1.0 × 10⁻⁶. 4 -6.0×10 4 g / mol, ash content 0.020-0.300wt%.

[0024] Furthermore, the polyethersulfone oligomer segments are introduced by a polyethersulfone potassium salt activating solution for forming the covalent linkages of the aromatic ether bonds, the polyethersulfone potassium salt activating solution being prepared through the following steps:

[0025] C1. The hydroxyl-terminated polyethersulfone oligomer used to introduce the polyethersulfone oligomer segments is added to N-methylpyrrolidone to prepare a hydroxyl-terminated polyethersulfone oligomer solution with a solid content of 5.00-30.00 wt% based on the dry basis mass of the hydroxyl-terminated polyethersulfone oligomer as a percentage of the total mass of the solution.

[0026] C2. Add anhydrous potassium carbonate to the hydroxyl-terminated polyethersulfone oligomer solution, wherein the molar ratio of anhydrous potassium carbonate to the terminal hydroxyl groups of the hydroxyl-terminated polyethersulfone oligomer is 0.80-2.00:1;

[0027] C3. Under industrial-grade nitrogen protection, the polyethersulfone potassium salt activation solution is activated at 120-160℃ for 0.5-2.0h to obtain the activated solution.

[0028] The water content of the polyethersulfone potassium salt activating solution is 20-500 mg / kg, the solid content based on the dry basis mass of the hydroxyl-terminated polyethersulfone oligomer as a percentage of the total mass of the activating solution is 5.00-30.00 wt%, and the undissolved matter is 0-0.50 wt%.

[0029] Furthermore, the p-dichlorophenyl polyphenylene sulfide has a terminal chlorine group content of 0.005-0.040 mmol / g, a molecular weight distribution coefficient of 1.8-4.5, and a water content of 0.005-0.100 wt%.

[0030] Furthermore, the p-dichlorophenyl polyphenylene sulfide has a melting point of 275-295℃, a crystallization temperature of 210-250℃, and a glass transition temperature of 88-125℃.

[0031] Furthermore, the apparent consumption ratio of the terminal hydroxyl groups is 30.00-95.00 mol%, and the apparent consumption ratio of the terminal hydroxyl groups is calculated according to the following formula:

[0032] Apparent consumption ratio of terminal hydroxyl groups = (n o -n e -n r ) / n o ×100%;

[0033] Where, n o n represents the amount of terminal hydroxyl groups contained in the hydroxyl-terminated polyethersulfone oligomer being fed. e n represents the amount of terminal hydroxyl groups in the polyethersulfone oligomer recovered from the extract after extraction of the final product in N-methylpyrrolidone at 80°C and a liquid-to-solid mass ratio of 20:1 for 4 hours. r This represents the amount of detectable terminal hydroxyl groups remaining in the insoluble matter after extraction.

[0034] This invention employs a design that covalently links polyphenylene sulfide (PPS) main segments with polyethersulfone (PES) oligomer segments introduced by hydroxyl-terminated PES oligomers via aryl ether bonds. This design primarily aims to achieve a synergistic balance between crystallinity regularity and chain stability. In existing technologies, to improve the heat resistance and crystallinity stability of PPS materials, a high degree of PPS segment regularity and proportion is typically maintained. However, this approach limits the space for introducing adjustable segments, resulting in insufficient space for segment composition adjustment and end-group consumption. To improve the stability of modified segments and the degree of segment composition adjustment, the introduction degree of PES oligomer segments may be increased, but excessive introduction can interfere with the PPS segment arrangement and affect the heat resistance. This invention, through the proportional matching of PPS main segments, PES oligomer segments, and aryl ether covalent bonds, allows the segment adjustment effect and the crystallinity and heat resistance to mutually correct each other, thereby balancing the mutually restrictive performance characteristics. Examples 1-4 use 2.00wt%, 7.00wt%, 10.00wt%, and 12.00wt% of hydroxyl-terminated polyethersulfone oligomers as dry basis feed ratios, respectively. Within this dry basis feed ratio range, by controlling the water content of the polyethersulfone potassium salt activating solution, the apparent consumption ratio of terminal hydroxyl groups, and the chain segment connection conditions, it is beneficial to form a matching relationship between crystallization thermal behavior, residual chlorine control, and melt flowability.

[0035] This invention also discloses a method for preparing p-dichlorophenyl polyphenyl sulfide, comprising the following steps:

[0036] S1. Provides hydroxyl-terminated polyethersulfone oligomers;

[0037] S2. Sodium sulfide nonahydrate, N-methylpyrrolidone, anhydrous lithium chloride and anhydrous sodium acetate are added to a closed pressure-resistant reactor equipped with a condenser and water separator. The reactor is dehydrated at 160-205℃ for 1.0-4.0 h under industrial-grade nitrogen protection. The dehydrated water is discharged after condensation and water separation to obtain a dehydrated sodium sulfide reaction system. The water content of the dehydrated system is 1.00-1.35 mol water / mol sodium sulfide.

[0038] S3. Add p-dichlorobenzene to the dehydrated sodium sulfide reaction system, wherein the molar ratio of p-dichlorobenzene to sodium sulfide is 1.005-1.050:1, react at 220-245℃ and under autogenous pressure for 0.5-2.0 h, then raise the temperature to 250-275℃ and react at autogenous pressure for 1.0-4.0 h, and obtain p-chlorophenyl-terminated polyphenylene sulfide prepolymer after solid-liquid separation, washing and drying;

[0039] S4. The hydroxyl-terminated polyethersulfone oligomer is added to N-methylpyrrolidone to prepare a hydroxyl-terminated polyethersulfone oligomer solution with a solid content of 5.00-30.00 wt% based on the dry basis mass of the hydroxyl-terminated polyethersulfone oligomer as a percentage of the total mass of the solution. Anhydrous potassium carbonate is added to the hydroxyl-terminated polyethersulfone oligomer solution and activated at 120-160°C under industrial-grade nitrogen protection for 0.5-2.0 h to obtain a polyethersulfone potassium salt activated solution; then, the p-chlorophenyl-terminated polyphenylene sulfide pre- The polyethersulfone potassium salt activating solution is added to the polymer, wherein the amount of the hydroxyl-terminated polyethersulfone oligomer added is 2.04-13.64 wt% of the dry basis mass of the p-chlorophenyl-terminated polyphenylene sulfide prepolymer, and the molar ratio of anhydrous potassium carbonate to the terminal hydroxyl groups of the hydroxyl-terminated polyethersulfone oligomer is 0.80-2.00:1. Under industrial-grade nitrogen protection, the reaction is carried out at 260-285℃ and autogenous pressure for 0.5-3.0 h to obtain a reaction product with covalent linkage of aryl ether bonds.

[0040] S5. The reaction product with covalent linkage of aromatic ether bonds is washed, filtered and dried to obtain the p-dichlorophenyl polyphenyl sulfide.

[0041] Unless otherwise stated, the amounts of substances relating to sodium sulfide in this specification are calculated as the amount of sodium sulfide nonhydrate converted to anhydrous sodium sulfide.

[0042] Furthermore, in step S2, the molar ratio of sodium sulfide nonahydrate, N-methylpyrrolidone, anhydrous lithium chloride, and anhydrous sodium acetate is 1:3.0-6.5:0.05-0.60:0.05-0.60.

[0043] Further, the washing in step S5 includes washing with deionized water, washing with 0.05-0.50 mol / L hydrochloric acid solution, and washing with deionized water again. Each deionized water wash is performed at a temperature of 60-95℃ for 0.2-2.0 h, and the total number of washes is 2-8. The drying temperature is 100-160℃ for 4.0-16.0 h. Both the deionized water wash and the hydrochloric acid solution wash are based on the mass of the solid product before drying, with a liquid-to-solid mass ratio of 5:1-20:1. The hydrochloric acid solution wash temperature is 25-80℃ for 0.2-2.0 h. After the second deionized water wash, the endpoint for inorganic salt elution is defined as a final wash solution conductivity not exceeding 50 μS / cm.

[0044] Furthermore, the total chlorine content of the p-dichlorophenyl polyphenylene sulfide obtained in step S5 is 200-1500 mg / kg, the ash content is 0.005-0.150 wt%, the residual N-methylpyrrolidone is 20-1000 mg / kg, and the weight-average molecular weight is 2.0 × 10⁻⁶. 4 -8.0×10 4 g / mol.

[0045] Furthermore, in the preparation of hydroxyl-terminated polyethersulfone oligomers, 4,4'-dihydroxydiphenyl sulfone, 4,4'-dichlorodiphenyl sulfone, anhydrous potassium carbonate, N-methylpyrrolidone, and toluene were added to a reaction vessel equipped with a stirrer, condenser, and water separator. Under industrial-grade nitrogen protection, azeotropic dehydration was carried out at 140-165℃ for 1.0-3.0 h. During the azeotropic dehydration process, toluene and the generated water were removed. Subsequently, the reaction system was heated to 170-190℃ for polycondensation for 2.0-6.0 h to obtain a reaction solution containing hydroxyl-terminated polyethersulfone oligomers. The azeotropic dehydration stage was controlled by the continuous removal of the aqueous phase from the water separator and a water content in the reaction solution dropping below 500 mg / kg as the entry condition for the polycondensation stage.

[0046] Further, the reaction solution containing hydroxyl-terminated polyethersulfone oligomers is added to deionized water for precipitation to obtain hydroxyl-terminated polyethersulfone oligomer precipitate. The precipitate is then washed sequentially with deionized water, followed by washing with a 0.05-0.50 mol / L hydrochloric acid solution, and then with deionized water again. After filtration, the precipitate is dried at 100-140℃ for 4.0-12.0 h to obtain hydroxyl-terminated polyethersulfone oligomers. These oligomers are used to prepare polyethersulfone potassium salt activation solutions or to add p-chlorophenyl-terminated polyphenylene sulfide prepolymers. The solid-liquid mass ratio of each wash of the hydroxyl-terminated polyethersulfone oligomer precipitate is 5:1-20:1. The residual potassium ion content, hydroxyl value, and terminal hydroxyl content of the filtered oligomers are used as quality control indicators for entering the activation step.

[0047] Further, the hydroxyl-terminated polyethersulfone oligomer obtained after precipitation, washing, filtration, and drying is added to N-methylpyrrolidone to prepare a hydroxyl-terminated polyethersulfone oligomer solution with a solid content of 5.00-30.00 wt%. Anhydrous potassium carbonate is added to the hydroxyl-terminated polyethersulfone oligomer solution, wherein the molar ratio of anhydrous potassium carbonate to the terminal hydroxyl groups of the hydroxyl-terminated polyethersulfone oligomer is 0.80-2.00:1. Activation is carried out at 120-160℃ for 0.5-2.0 h under industrial-grade nitrogen protection to obtain a water content of 20-500 mg / kg. A potassium ethersulfone activating solution with a solid content of 5.00-30.00 wt% and an undissolved content of 0-0.50 wt% is prepared. The potassium ethersulfone activating solution is added to a sealed pressure-resistant reactor containing a p-chlorophenyl-terminated polyphenylene sulfide prepolymer, wherein the amount of the hydroxyl-terminated polyethersulfone oligomer added is 2.04-13.64 wt% of the dry basis mass of the p-chlorophenyl-terminated polyphenylene sulfide prepolymer. The reaction is carried out at 260-285°C under industrial-grade nitrogen protection and under the system's autogenous pressure for 0.5-3.0 h to obtain a reaction product with covalent linkage of aromatic ether bonds. The polyethersulfone potassium salt activation solution was filtered through a 100μm metal filter before addition, and the undissolved matter was calculated based on the difference in dry weight before and after filtration. When adding the polyethersulfone potassium salt activation solution to the sealed pressure-resistant reactor, the addition time was 10-60 minutes. During the addition process, the reaction system temperature was maintained at 240-270℃, and after addition, the temperature was raised to 260-285℃ for the chain linking reaction. The water content of the polyethersulfone potassium salt activation solution was determined using the Karl Fischer method, and the solid content and undissolved matter were determined according to the definitions described above in this specification.

[0048] Further, the reaction product with covalently linked aromatic ether bonds is sequentially washed with deionized water, then with a 0.05-0.50 mol / L hydrochloric acid solution, and finally with deionized water again. The hydrochloric acid solution is prepared by mixing hydrochloric acid and deionized water. Each deionized water wash is performed at a temperature of 60-95°C for 0.2-2.0 h, with a total of 2-8 washes. The washed product is then filtered and dried at 100-160°C for 4.0-16.0 h to obtain p-dichlorophenyl polyphenylene sulfide. Filtration is performed using a metal filter screen or solvent-resistant filter cloth with a pore size of 20-100 μm. Drying is performed using hot air drying or vacuum drying. When vacuum drying is used, the vacuum level is -0.08 MPa to -0.10 MPa, and the drying endpoint is when the product water content is no higher than 0.100 wt%.

[0049] This invention employs a stepwise preparation method for p-chlorophenyl-terminated polyphenylene sulfide prepolymers and the introduction of hydroxyl-terminated polyethersulfone oligomers in the presence of anhydrous potassium carbonate. This method is primarily used to achieve, fix, or amplify the aforementioned synergistic effects. Existing technologies, while simply extending the polyphenylene sulfide polymerization process can improve chain growth, may lead to decreased processing fluidity and difficulty in controlling residual terminal chlorine. Conversely, simply reducing the molecular weight to improve melt processing can easily result in high levels of terminal chlorine groups and insufficient structural stability. This invention, through control of the sodium sulfide dehydration reaction system, control of the p-dichlorobenzene to sodium sulfide ratio, segmented prepolymerization and polymerization, addition of hydroxyl-terminated polyethersulfone oligomers, and activation reaction with anhydrous potassium carbonate, coordinates end-group consumption, chain segment connection, and post-treatment purification within the same process chain, thereby achieving a simultaneous balance between low residual chlorine and processing fluidity. In this process, the terminal chlorine groups in the p-chlorophenyl-terminated polyphenylene sulfide prepolymer serve as acceptor end groups for the chain linkage reaction, while the aryloxy potassium end groups in the polyethersulfone potassium salt activation solution serve as donor end groups. Upon contact in a high-temperature N-methylpyrrolidone system, an end-group substitution reaction occurs, causing polyethersulfone oligomer segments to attach to the polyphenylene sulfide main chain segment or end group position via aryl ether bonds. After the reaction, inorganic salts, residual potassium carbonate, and extractable oligomers are removed by water washing and acid washing, resulting in a higher retention rate of polyethersulfone oligomer segments in the final product and a lower content of terminal chlorine groups compared to the prepolymer before the reaction. Since the prepolymer and the final product are samples from different stages with different molecular weight distributions, and the chain segment connection and post-processing will also change the proportion of extractable low molecular weight components, the content of terminal chlorine groups in each stage should be determined independently according to the total chlorine content and free chlorine content of the corresponding stage sample. Simple material balance should not be made based on the content of terminal chlorine groups in the prepolymer, the amount of hydroxyl-terminated polyethersulfone oligomer fed, or the apparent consumption ratio of terminal hydroxyl groups.

[0050] The main chain segments of polyphenylene sulfide (PPS) primarily serve to maintain crystallinity, provide heat resistance, and act as the main framework. However, excessively high proportions or excessive retention of terminal chlorine groups can weaken the regulation of chain composition and the space consumed by terminal groups, making the processing more sensitive to molecular weight and residual chlorine. The PPS oligomer segments introduced by hydroxyl-terminated PPS oligomers mainly provide terminal hydroxyl reaction sites and regulate chain composition. However, their presence alone or excessive introduction may interfere with the regular crystallization of PPS due to differences in chain flexibility and sulfone ether structure. This invention addresses these issues by controlling the content of PPS oligomer segments, the apparent consumption ratio of terminal hydroxyl groups, the water content of the PPS potassium salt activation solution, and the reaction sequence with the p-chlorophenyl-terminated PPS prepolymer. This allows the two types of segments to mutually correct each other through proportional matching and aryl ether bond linkage, ultimately balancing their mutually restrictive properties.

[0051] Beneficial technical effects

[0052] 1. By introducing polyethersulfone oligomer segments formed by hydroxyl-terminated polyethersulfone oligomers into the polyphenylene sulfide main chain segment and covalently linking the two types of segments through aryl ether bonds, the tendency of segment migration and interface separation caused by simple physical blending can be reduced, the retention stability of polyethersulfone oligomer segments under specified N-methylpyrrolidone extraction conditions can be improved, and the component distribution uniformity of the final product powder can be improved.

[0053] 2. By controlling the content ratio of polyphenylene sulfide main chain segment and polyethersulfone oligomer chain segment, excessive introduction of polyethersulfone oligomer chain segment can avoid excessive interference with the crystal regularity of polyphenylene sulfide, while retaining sufficient terminal hydroxyl reaction sites, so that heat resistance, glass transition behavior and chain stability can form a good synergistic balance.

[0054] 3. By segmentally controlling the dehydration of sodium sulfide nonahydrate, the molar ratio of dichlorobenzene to sodium sulfide, and the prepolymerization and polymerization temperatures, the level of terminal chlorine groups can be adjusted while forming the p-chlorophenyl-terminated polyphenylene sulfide prepolymer. This allows the subsequent hydroxyl-terminated polyethersulfone oligomer to be introduced with a clearer reaction window, which is beneficial for reducing residual chlorine and maintaining processing fluidity.

[0055] 4. By controlling the solid content, water content, undissolved matter, and anhydrous potassium carbonate content of the polyethersulfone potassium salt activation solution, the operability of hydroxyl-terminated polyethersulfone oligomer segments participating in the linkage can be improved, the influence of moisture and undissolved matter on the homogeneity of the reaction system can be reduced, and the reproducibility of segment linkage, residue control, and post-processing purification can be improved.

[0056] 5. By combining washing with deionized water, washing with hydrochloric acid solution, washing with deionized water again, and drying, the influence of inorganic salts, potassium ions, residual solvents, and moisture on the final product can be reduced, keeping the ash content, residual N-methylpyrrolidone, and water content at controllable levels, thereby improving subsequent melt processing and long-term stability. Attached Figure Description

[0057] Figure 1 The raw FTIR absorbance spectra of Example 1, Comparative Example 10, and Comparative Example 11 are shown.

[0058] Figure 2 The FTIR baseline-corrected absorbance spectra of Example 1, Comparative Example 10, and Comparative Example 11 are shown.

[0059] Figure 3 The DSC heating heat flux curves are for Examples 1, 4, Comparative Example 7, and Comparative Example 9.

[0060] Figure 4 The graphs show the relationship between total chlorine content and melt flow rate under different dry basis ratios of hydroxyl-terminated polyethersulfone oligomers and corresponding process conditions in Examples 1-4.

[0061] Figure 5 This is a comparison of macroscopic optical photographs of the final product of Example 1 and the final product of Comparative Example 11; wherein, Figure 5 Figure a in the image is a macroscopic optical photograph of the final product of Example 1, in powder form: p-dichlorophenyl polyphenyl sulfide. Figure 5 Figure b in the figure is a macroscopic optical photograph of the final product of Comparative Example 11.

[0062] Figure 6 The images show a comparison of the low-magnification, medium-magnification, and high-magnification SEM morphology and SEM-EDS elemental surface distribution of the final products of Example 1 and Comparative Example 11. In the images, a, c, e, and g correspond to Example 1, and b, d, f, and h correspond to Comparative Example 11. Detailed Implementation

[0063] To make the objectives, technical solutions, and advantages of the embodiments of the present invention clearer, the technical solutions of the embodiments of the present invention will be clearly and completely described below with reference to the accompanying drawings. In the following embodiments, the mass of the p-chlorophenyl-terminated polyphenylene sulfide prepolymer is the dry basis mass after solid-liquid separation, washing, and drying; the amount of hydroxyl-terminated polyethersulfone oligomer added is based on the dry basis mass of the prepolymer; the ratio of polyphenylene sulfide main chain segment to polyethersulfone oligomer chain segment in the embodiments is the designed ratio calculated based on the dry basis mass of the above two types of materials; the chain segment retention rate after N-methylpyrrolidone extraction is an independently evaluated result, and the designed ratio is not corrected. Unless otherwise stated, the amount of hydroxyl-terminated polyethersulfone oligomer added in the comparative examples is also based on the dry basis mass of the p-chlorophenyl-terminated polyphenylene sulfide prepolymer. The amount of sodium sulfide involved in each embodiment and comparative example is converted according to the anhydrous sodium sulfide contained in sodium sulfide nonhydrate.

[0064] Example 1

[0065] In terms of overall preparation scale and product form, this embodiment prepares powdered p-dichlorophenyl polyphenylene sulfide. Sodium sulfide is added based on 10.00 mol of sodium sulfide nonahydrate, and 1000.00 g of p-chlorophenyl-terminated polyphenylene sulfide prepolymer dry basis is used as the target for subsequent chain segment linkage reactions. Based on the dry basis mass of the added materials, the designed ratio of polyphenylene sulfide main chain segment to polyethersulfone oligomer chain segment in this embodiment is 98.00 wt%: 2.00 wt%.

[0066] Raw material, component, or material specifications: 4,4'-dihydroxydiphenyl sulfone is a commercially available chemically pure raw material with a purity ≥99.0%; 4,4'-dichlorodiphenyl sulfone is a commercially available chemically pure raw material with a purity ≥99.0%; anhydrous potassium carbonate is a commercially available analytical grade raw material with a moisture content ≤0.20wt%; N-methylpyrrolidone is a commercially available polymerization-grade solvent with a moisture content ≤300mg / kg; toluene is a commercially available analytical grade solvent with a moisture content ≤300mg / kg; sodium sulfide nonahydrate is a commercially available industrial-grade raw material, and the effective sodium sulfide content is calculated using the iodometric method for the calculation of feed content; anhydrous lithium chloride and anhydrous sodium acetate are both commercially available chemically pure raw materials; industrial-grade nitrogen has a purity ≥99.5%; and deionized water has a conductivity ≤10μS / cm.

[0067] Step 1: Preparation of hydroxyl-terminated polyethersulfone oligomers. 1.20 mol of 4,4'-dihydroxydiphenyl sulfone, 1.00 mol of 4,4'-dichlorodiphenyl sulfone, 1.26 mol of anhydrous potassium carbonate, 2200 g of N-methylpyrrolidone, and 260 g of toluene were added to a reaction vessel equipped with a stirrer, water separator, and nitrogen inlet. Industrial-grade nitrogen was introduced for 30 min, followed by stirring at 300 rpm. The reaction system was heated to 140 °C and refluxed for azeotropic dehydration for 1.0 h, continuously removing toluene and water. Subsequently, the temperature was increased to 170 °C at 2 °C / min and polycondensation was carried out for 2.0 h. The reaction solution was cooled to 80 °C, and precipitated with 5 times its mass of deionized water. The precipitate was washed successively with deionized water, 0.05 mol / L hydrochloric acid solution, and deionized water. After filtration, it was dried at 100 °C for 4.0 h to obtain hydroxyl-terminated polyethersulfone oligomers. The hydroxyl-terminated polyethersulfone oligomer in this embodiment has a number-average molecular weight of 1400 g / mol, a hydroxyl value of 80 mg KOH / g, a terminal hydroxyl content of 1.43 mmol / g, and a residual potassium ion content of 1000 mg / kg.

[0068] Step 2: Preparation of p-chlorophenyl-terminated polyphenylene sulfide prepolymer. 10.00 mol sodium sulfide nonahydrate, 30.00 mol N-methylpyrrolidone, 0.50 mol anhydrous lithium chloride, and 0.50 mol anhydrous sodium acetate were added to a sealed, pressure-resistant reactor. Industrial-grade nitrogen was introduced for purging for 30 min, and the mixture was dehydrated at 160℃ for 1.0 h. The dehydrated water was condensed and discharged, resulting in a water content of 1.35 mol water / mol sodium sulfide. Subsequently, 10.50 mol p-dichlorobenzene was added, and the reaction was carried out at 220℃ under autogenous pressure for 0.5 h. The temperature was then increased to 250℃ at 2℃ / min, and the reaction was continued under autogenous pressure for 1.0 h. After the reaction, the temperature was lowered to below 120℃, and the mixture was subjected to solid-liquid separation, washed twice with deionized water at 60℃, and dried at 120℃ for 6.0 h to obtain the p-chlorophenyl-terminated polyphenylene sulfide prepolymer. In this embodiment, the p-chlorophenyl-terminated polyphenylene sulfide prepolymer has a terminal chlorine group content of 0.180 mmol / g and a weight-average molecular weight of 1.0 × 10⁻⁶. 4g / mol, ash content 0.300wt%.

[0069] Step 3: Chain segment linkage reaction. 1000.00 g of p-chlorophenyl-terminated polyphenylene sulfide prepolymer (dry weight) was placed in a sealed, pressure-resistant reactor. 20.41 g of hydroxyl-terminated polyethersulfone oligomer was added to N-methylpyrrolidone to prepare a hydroxyl-terminated polyethersulfone oligomer solution with a solid content of 5.00 wt%. 0.0233 mol of anhydrous potassium carbonate was added at a molar ratio of 0.80:1 to the terminal hydroxyl groups. The mixture was activated at 120°C for 0.5 h under industrial-grade nitrogen protection to obtain a polyethersulfone potassium salt activation solution. This activation solution had a water content of 500 mg / kg, a solid content of 5.00 wt%, and undissolved matter of 0.50 wt%. The polyethersulfone potassium salt activation solution was added to the reactor containing the p-chlorophenyl-terminated polyphenylene sulfide prepolymer within 10 min, and the reaction was carried out at 260°C under industrial-grade nitrogen protection and autogenous pressure for 0.5 h.

[0070] Step 4: Washing, filtering, and drying. The reaction product was cooled to 120℃ and discharged. A first wash was performed with deionized water at 60℃ for 0.2 hours (liquid:solid mass ratio 5:1). Subsequently, it was washed with 0.05 mol / L hydrochloric acid solution for 0.2 hours (liquid:solid mass ratio 5:1), followed by a second wash with deionized water at 60℃. The total number of deionized water washes was two. The conductivity of the final wash solution was 50 μS / cm. The filtered solid was dried at 100℃ for 4.0 hours to obtain p-dichlorophenyl polyphenylene sulfide.

[0071] The quality testing methods and results for this embodiment were as follows: The weight-average molecular weight of the product was determined by high-temperature volume exclusion chromatography; the melting point, crystallization temperature, and glass transition temperature were determined by differential scanning calorimetry; the total chlorine content was determined by combustion ion chromatography; the ash content was determined by ashing; the residual N-methylpyrrolidone was determined by headspace gas chromatography; and the water content was determined by Karl Fischer titration. The quality control results were: total chlorine content 1500 mg / kg, ash content 0.150 wt%, residual N-methylpyrrolidone 1000 mg / kg, and weight-average molecular weight 2.0 × 10⁻⁶. 4 g / mol, terminal chlorine group content 0.040 mmol / g, molecular weight distribution coefficient 4.5, water content 0.100 wt%, melting point 295℃, crystallization temperature 250℃, glass transition temperature 88℃, and apparent consumption ratio of terminal hydroxyl groups is 30.00 mol.

[0072] The features and application scenarios of this embodiment are as follows: This embodiment adopts a scheme with a low content of polyethersulfone oligomer segments, a high proportion of dichlorobenzene, a short chain connection time, and a mild washing and drying intensity. The product maintains a high proportion of polyphenylene sulfide main chain segments and a high melt flow level. It is suitable for basic powder preparation scenarios where the retention of polyphenylene sulfide main crystal is required and further optimization of purification conditions is still needed.

[0073] Example 2

[0074] Raw materials and proportions: In this embodiment, 10.00 mol sodium sulfide nonahydrate was used as the sulfur source to prepare p-dichlorophenyl polyphenylene sulfide. Based on the dry weight of the feed materials, the designed ratio of the polyphenylene sulfide main chain segment to the polyethersulfone oligomer chain segment in this embodiment is 88.00 wt%: 12.00 wt%. 4,4'-dihydroxydiphenyl sulfone, 4,4'-dichlorodiphenyl sulfone, anhydrous potassium carbonate, N-methylpyrrolidone, toluene, p-dichlorobenzene, sodium sulfide nonahydrate, anhydrous lithium chloride, and anhydrous sodium acetate were all commercially available or purchased raw materials. The aromatic monomers had a purity ≥99.0%, the anhydrous salt moisture content ≤0.20 wt%, the N-methylpyrrolidone moisture content ≤200 mg / kg, and the industrial-grade nitrogen gas had a purity ≥99.5%.

[0075] In the preparation process, 1.04 mol of 4,4'-dihydroxydiphenyl sulfone, 1.00 mol of 4,4'-dichlorodiphenyl sulfone, 1.456 mol of anhydrous potassium carbonate, 2500 g of N-methylpyrrolidone, and 300 g of toluene were added to a reaction vessel. Under industrial-grade nitrogen protection and stirring at 350 rpm, the mixture was heated to 165 °C and refluxed for azeotropic dehydration for 3.0 h. After removing toluene and water, the mixture was heated to 190 °C for polycondensation for 6.0 h. The reaction solution was precipitated with deionized water, washed with deionized water, washed with 0.50 mol / L hydrochloric acid solution, washed with deionized water again, and filtered. The resulting product was then dried at 140 °C for 12.0 h to obtain hydroxyl-terminated polyethersulfone oligomers. These hydroxyl-terminated polyethersulfone oligomers had a number-average molecular weight of 7400 g / mol, a hydroxyl value of 15 mg KOH / g, a terminal hydroxyl content of 0.27 mmol / g, and a residual potassium ion content of 20 mg / kg.

[0076] In the post-processing step, 10.00 mol of sodium sulfide nonahydrate, 65.00 mol of N-methylpyrrolidone, 6.00 mol of anhydrous lithium chloride, and 6.00 mol of anhydrous sodium acetate were added to a sealed pressure-resistant reactor. The reactor was dehydrated at 205℃ for 4.0 h under industrial-grade nitrogen protection. The dehydrated water was discharged after condensation and separation, resulting in a water content of 1.00 mol water / mol sodium sulfide in the dehydrated system. Then, 10.05 mol of p-dichlorobenzene was added, and the reaction was carried out at 245℃ under autogenous pressure for 2.0 h. The temperature was then increased to 275℃ under autogenous pressure for another 4.0 h. After the reaction, the temperature was lowered to below 120℃, followed by solid-liquid separation, washing four times with deionized water at 95℃, and drying at 140℃ for 8.0 h to obtain a p-chlorophenyl-terminated polyphenylene sulfide prepolymer. The prepolymer had a terminal chlorine group content of 0.020 mmol / g and a weight-average molecular weight of 6.0 × 10⁻⁶. 4 g / mol, ash content 0.020wt%.

[0077] For quality inspection or performance testing, 1000.00g of dry p-chlorophenyl-terminated polyphenylene sulfide prepolymer was taken, and 136.36g of hydroxyl-terminated polyethersulfone oligomer was added to N-methylpyrrolidone to prepare a hydroxyl-terminated polyethersulfone oligomer solution with a solid content of 30.00wt%. 0.0736mol of anhydrous potassium carbonate was added at a molar ratio of 2.00:1 to the terminal hydroxyl groups, and the mixture was activated at 160℃ for 2.0h to obtain a polyethersulfone potassium salt activation solution with a water content of 20mg / kg, a solid content of 30.00wt%, and 0.00wt% undissolved matter. The polyethersulfone potassium salt activation solution was added to a prepolymer reactor and reacted at 285℃ under industrial-grade nitrogen protection and autogenous pressure for 3.0h. The reaction product was sequentially washed with deionized water at 95℃, followed by washing with 0.50 mol / L hydrochloric acid solution, and then again with deionized water at 95℃. Each deionized water wash lasted 2.0 h, for a total of 8 washes. The liquid-to-solid mass ratio was 20:1, and the conductivity of the final wash solution was 20 μS / cm. After filtration, the product was dried at 160℃ for 16.0 h. The quality control results were: total chlorine content 200 mg / kg, ash content 0.005 wt%, residual N-methylpyrrolidone 20 mg / kg, and weight-average molecular weight 8.0 × 10⁻⁶. 4 g / mol, terminal chlorine group content 0.005 mmol / g, molecular weight distribution coefficient 1.8, water content 0.005 wt%, melting point 275℃, crystallization temperature 210℃, glass transition temperature 125℃, and apparent consumption ratio of terminal hydroxyl groups is 95.00 mol.

[0078] The features of this embodiment are that it uses a combination of high polyethersulfone oligomer segment content, sufficient activation treatment, high reaction temperature and strong washing and drying. The product has low residual chlorine, ash, residual N-methylpyrrolidone and water content, which is suitable for the preparation of heat-resistant engineering plastic powders with high requirements for low ion residue, low solvent residue and high stability of modified segments.

[0079] Example 3

[0080] The key parameters used in this embodiment are as follows: the molar ratio of 4,4'-dihydroxydiphenyl sulfone to 4,4'-dichlorodiphenyl sulfone is 1.12:1; the molar ratio of anhydrous potassium carbonate to 4,4'-dihydroxydiphenyl sulfone is 1.22:1; the molar ratio of sodium sulfide nonahydrate, N-methylpyrrolidone, anhydrous lithium chloride, and anhydrous sodium acetate is 1:4.8:0.30:0.35; the molar ratio of p-dichlorobenzene to sodium sulfide is 1.025:1; the amount of hydroxyl-terminated polyethersulfone oligomer added is 7.53 wt% of the dry basis mass of the p-chlorophenyl-terminated polyphenylene sulfide prepolymer; calculated based on the dry basis mass of the feed, the designed ratio of polyphenylene sulfide main chain segment to polyethersulfone oligomer chain segment in this embodiment is 93.00 wt%:7.00 wt%.

[0081] The specific preparation process is as follows: 1.12 mol of 4,4'-dihydroxydiphenyl sulfone, 1.00 mol of 4,4'-dichlorodiphenyl sulfone, 1.366 mol of anhydrous potassium carbonate, 2300 g of N-methylpyrrolidone, and 280 g of toluene were added to a reaction vessel. Industrial-grade nitrogen was introduced and the mixture was stirred at 320 rpm. The mixture was refluxed at 152 °C for azeotropic dehydration for 2.0 h, followed by polycondensation at 182 °C for 4.0 h at a rate of 2 °C / min. The reaction solution was added to deionized water for precipitation. The precipitate was washed successively with deionized water, 0.20 mol / L hydrochloric acid solution, and deionized water. After filtration, the precipitate was dried at 120 °C for 8.0 h to obtain hydroxyl-terminated polyethersulfone oligomers. The number-average molecular weight of this hydroxyl-terminated polyethersulfone oligomer was 3000 g / mol, the hydroxyl value was 38 mg KOH / g, the terminal hydroxyl content was 0.68 mmol / g, and the residual potassium ion content was 300 mg / kg.

[0082] A p-chlorophenyl-terminated polyphenylene sulfide prepolymer was prepared as follows: 10.00 mol sodium sulfide nonahydrate, 48.00 mol N-methylpyrrolidone, 3.00 mol anhydrous lithium chloride, and 3.50 mol anhydrous sodium acetate were added to a sealed pressure-resistant reactor and dehydrated at 182℃ for 2.5 h under industrial-grade nitrogen protection. The dehydrated water was discharged after condensation and separation, resulting in a water content of 1.18 mol water / mol sodium sulfide in the system. 10.25 mol p-dichlorobenzene was added to the dehydrated sodium sulfide reaction system, and the reaction was carried out at 235℃ under autogenous pressure for 1.2 h. The temperature was then increased to 260℃ under autogenous pressure for another 2.5 h. After the reaction, the temperature was lowered to below 120℃, and the mixture was subjected to solid-liquid separation, washed three times with deionized water at 78℃, and dried at 130℃ for 8.0 h to obtain a prepolymer with a terminal chlorine group content of 0.085 mmol / g and a weight-average molecular weight of 3.5 × 10⁻⁶. 4 p-Chlorophenyl-terminated polyphenylene sulfide prepolymer with g / mol and ash content of 0.120 wt%.

[0083] The chain segment linkage and purification process is as follows: 1000.00g of dry p-chlorophenyl-terminated polyphenylene sulfide prepolymer was taken, and 75.27g of hydroxyl-terminated polyethersulfone oligomer was added to N-methylpyrrolidone to prepare a hydroxyl-terminated polyethersulfone oligomer solution with a solid content of 18.00wt%. 0.0665mol of anhydrous potassium carbonate was added at a molar ratio of 1.30:1 to the terminal hydroxyl groups, and the mixture was activated at 140℃ for 1.2h under industrial-grade nitrogen protection to obtain a polyethersulfone potassium salt activation solution with a water content of 180mg / kg, a solid content of 18.00wt%, and 0.18wt% undissolved matter. This activation solution was added to the prepolymer reactor and reacted at 272℃ under industrial-grade nitrogen protection and autogenous pressure for 1.6h. The reaction product was washed with deionized water at 78℃, washed with 0.20 mol / L hydrochloric acid solution, and washed with deionized water at 78℃ for 1.0 h each time, for a total of 5 washes. The liquid-to-solid mass ratio was 10:1, and the conductivity of the final wash solution was 35 μS / cm. After filtration, the product was dried at 130℃ for 8.0 h to obtain p-dichlorophenyl polyphenylene sulfide.

[0084] The quality testing methods and results are as follows: High-temperature volume exclusion chromatography showed a weight-average molecular weight of 5.0 × 10⁻⁶. 4g / mol, molecular weight distribution coefficient of 2.7; combustion ion chromatography test showed total chlorine content of 840 mg / kg; end-group titration conversion showed end-chlorine group content of 0.020 mmol / g; ashing test showed ash content of 0.060 wt%; headspace gas chromatography test showed residual N-methylpyrrolidone of 420 mg / kg; Karl Fischer titration test showed water content of 0.040 wt%; differential scanning calorimetry showed melting point of 286℃, crystallization temperature of 232℃, glass transition temperature of 106℃; apparent consumption of terminal hydroxyl groups was 62.00 mol.

[0085] The applicable scenarios of this embodiment are as follows: This embodiment uses medium polyethersulfone oligomer segment content, medium molecular weight prepolymer and medium activation strength. The preparation conditions maintain a balance between segment connection, residual chlorine control and melt processing. It is suitable for conventional injection molding, pre-extrusion powder preparation and polyphenylene sulfide preparation scenarios that require consideration of thermal properties and process stability.

[0086] Example 4

[0087] I. Preparation Object and Raw Material State

[0088] Using 10.00 mol sodium sulfide nonahydrate as the sulfur source and 1000.00 g of p-chlorophenyl-terminated polyphenylene sulfide prepolymer dry basis as the standard for chain linking reaction, p-dichlorophenyl polyphenylene sulfide was prepared. Based on the dry basis mass of the feed materials, the designed ratio of polyphenylene sulfide main chain segment to polyethersulfone oligomer chain segment in this embodiment was 90.00 wt%: 10.00 wt%. All aromatic monomers were commercially available chemically pure or analytically pure raw materials with a purity ≥99.0%; anhydrous salt moisture ≤0.20 wt%; industrial-grade nitrogen purity ≥99.5%; and deionized water conductivity ≤10 μS / cm.

[0089] II. Preparation of hydroxyl-terminated polyethersulfone oligomers: 1.16 mol of 4,4'-dihydroxydiphenyl sulfone, 1.00 mol of 4,4'-dichlorodiphenyl sulfone, 1.508 mol of anhydrous potassium carbonate, 2400 g of N-methylpyrrolidone, and 290 g of toluene were added to a reaction vessel and stirred at 330 rpm under industrial-grade nitrogen protection. The reaction system was refluxed at 160 °C for azeotropic dehydration for 2.6 h. After removing toluene and the generated water, the temperature was raised to 186 °C for polycondensation for 5.0 h. The resulting reaction solution was precipitated with deionized water. The precipitate was washed with deionized water, washed with 0.35 mol / L hydrochloric acid solution, washed with deionized water, and filtered. It was then dried at 135 °C for 10.0 h to obtain hydroxyl-terminated polyethersulfone oligomers. The number-average molecular weight of this oligomer was 4350 g / mol, the hydroxyl value was 26 mg KOH / g, the terminal hydroxyl content was 0.46 mmol / g, and the residual potassium ion content was 80 mg / kg.

[0090] III. Preparation of p-chlorophenyl-terminated polyphenylene sulfide prepolymer: 10.00 mol sodium sulfide nonahydrate, 56.00 mol N-methylpyrrolidone, 5.00 mol anhydrous lithium chloride, and 4.50 mol anhydrous sodium acetate were added to a sealed pressure-resistant reactor. After purging with industrial-grade nitrogen, the mixture was dehydrated at 195℃ for 3.2 h. The dehydrated water was discharged after condensation and separation. The water content of the system after dehydration was 1.08 mol water / mol sodium sulfide. 10.40 mol p-dichlorobenzene was added, and the reaction was carried out at 240℃ under autogenous pressure for 1.6 h. The temperature was then increased to 270℃ and the reaction was carried out under autogenous pressure for 3.2 h. After the reaction, the temperature was lowered to below 120℃, and the mixture was subjected to solid-liquid separation, washed four times with deionized water at 90℃, and dried at 140℃ for 10.0 h to obtain the p-chlorophenyl-terminated polyphenylene sulfide prepolymer. The prepolymer has a terminal chlorine group content of 0.050 mmol / g and a weight-average molecular weight of 5.0 × 10⁻⁶. 4 g / mol, ash content 0.050wt%.

[0091] IV. Segment Linkage, Washing, and Drying: 111.11 g of hydroxyl-terminated polyethersulfone oligomer was added to N-methylpyrrolidone to form a hydroxyl-terminated polyethersulfone oligomer solution with a solid content of 24.00 wt%. 0.0818 mol of anhydrous potassium carbonate was added to this solution, with a molar ratio of anhydrous potassium carbonate to terminal hydroxyl groups of 1.60:1. The solution was activated at 150 °C for 1.6 h to obtain a polyethersulfone potassium salt activation solution with a water content of 80 mg / kg, a solid content of 24.00 wt%, and 0.06 wt% undissolved matter. This polyethersulfone potassium salt activation solution was added to a reactor containing 1000.00 g of dry p-chlorophenyl-terminated polyphenylene sulfide prepolymer and reacted at 280 °C under industrial-grade nitrogen protection and autogenous pressure for 2.4 h. The reaction product was washed sequentially with deionized water at 90℃, 0.35 mol / L hydrochloric acid solution, and then with deionized water at 90℃. Each deionized water wash lasted 1.5 h, and the total number of washes was 6. The liquid-to-solid mass ratio was 15:1. The conductivity of the final wash solution was 25 μS / cm. After filtration, the product was dried at 145℃ for 12.0 h to obtain p-dichlorophenyl polyphenylene sulfide.

[0092] V. Quality Testing Methods and Results: The product was analyzed using high-temperature volume exclusion chromatography, differential scanning calorimetry, combustion ion chromatography, ashing, headspace gas chromatography, Karl Fischer titration, and end-group titration. The quality control results were: total chlorine content 320 mg / kg, ash content 0.020 wt%, residual N-methylpyrrolidone 80 mg / kg, and weight-average molecular weight 7.2 × 10⁻⁶. 4 g / mol, terminal chlorine group content 0.008 mmol / g, molecular weight distribution coefficient 2.1, water content 0.012 wt%, melting point 279℃, crystallization temperature 218℃, glass transition temperature 118℃, and apparent consumption ratio of terminal hydroxyl groups is 80.00 mol.

[0093] VI. Process Features and Application Directions of this Embodiment

[0094] This embodiment employs a combination of relatively high polyethersulfone oligomer segment content, sufficient polyethersulfone potassium salt activation treatment, and strong purification and drying, while retaining a high proportion of polyphenylene sulfide main chain segments. This approach is suitable for preparing modified polyphenylene sulfide materials that have high requirements for residual chlorine, residual solvent, thermal properties, and molding stability.

[0095] Comparative Example 1: Same as Example 1, except that the molar ratio of 4,4'-dihydroxydiphenyl sulfone to 4,4'-dichlorodiphenyl sulfone in step 1 was adjusted to 1.30:1.

[0096] Comparative Example 2: Same as Example 1, except that the molar ratio of anhydrous potassium carbonate to 4,4'-dihydroxydiphenyl sulfone was adjusted to 0.80:1 in step 1.

[0097] Comparative Example 3: Same as Example 1, except that the molar ratio of dichlorobenzene to sodium sulfide was adjusted to 1.080:1 in step 2.

[0098] Comparative Example 4: Same as Example 1, except that the water content of the system after dehydration in step 2 was adjusted to 1.60 mol water / mol sodium sulfide.

[0099] Comparative Example 5: Same as Example 1, except that the polymerization temperature in the second stage of step 2 was adjusted to 245°C.

[0100] Comparative Example 6: Same as Example 1, except that the chain segment linkage reaction temperature in step 3 was adjusted to 245°C.

[0101] Comparative Example 7: Same as Example 1, except that the chain segment connection reaction temperature in step 3 was adjusted to 300°C.

[0102] Comparative Example 8: Same as Example 1, except that washing with 0.05 mol / L hydrochloric acid solution was not performed in step 4.

[0103] Comparative Example 9: Same as Example 1, except that no hydroxyl-terminated polyethersulfone oligomer was added in step 3, and the hydroxyl-terminated polyethersulfone oligomer obtained in step 1 did not enter the subsequent chain linking reaction. This comparative example was used to examine the effect of chain segment sizing when no hydroxyl-terminated polyethersulfone oligomer was introduced.

[0104] Comparative Example 10: Same as Example 1, except that in step 3, 20.41 g of hydroxyl-terminated polyethersulfone oligomer was prepared into an unactivated N-methylpyrrolidone solution with a solid content of 5.00 wt% and then directly added to the p-chlorophenyl-terminated polyphenylene sulfide prepolymer, without adding anhydrous potassium carbonate for hydroxyl activation. This comparative example was used to investigate the effect of polyethersulfone potassium salt activation on segment linkage.

[0105] Comparative Example 11: Same as Example 1, except that the activation of potassium polyethersulfone and in-situ segment linkage in step 3 were not performed; the p-chlorophenyl-terminated polyphenylene sulfide prepolymer obtained in step 2 of Example 1 was first treated under the washing, filtering, and drying conditions of step 4 to obtain polyphenylene sulfide powder. Then, 20.41 g of hydroxyl-terminated polyethersulfone oligomer and 1000.00 g of the polyphenylene sulfide powder were melt-mixed at 300°C for 0.5 h under industrial-grade nitrogen protection. This comparative example was used to examine the synergistic relationship between the segment linkage sequence and the polyphenylene sulfide main chain segment and the polyethersulfone oligomer segment.

[0106] Characterization and performance testing:

[0107] The number-average molecular weight, hydroxyl value, terminal hydroxyl content, and residual potassium ion content of hydroxyl-terminated polyethersulfone oligomers were determined. The number-average molecular weight was determined by high-temperature volume exclusion chromatography; the hydroxyl value was determined by acetylation back titration; the terminal hydroxyl content was converted by dividing the hydroxyl value by 56.1, and the unit was mmol / g; the residual potassium ion content was determined by inductively coupled plasma atomic emission spectrometry after acid digestion.

[0108] High-temperature volume exclusion chromatography was performed on the p-dichlorophenyl polyphenylene sulfide samples from Examples 1-4 to evaluate the effects of weight-average molecular weight, number-average molecular weight, and molecular weight distribution coefficient (MDC) on chain segmentation and processing fluidity. The principle is that the polymer is separated by volume according to hydrodynamics, and the molecular weight is calculated using a calibration curve. High-temperature testing procedures were established according to GB / T36214.1-2018 and GB / T36214.4-2018. The sample was dissolved at 210°C using 1-chloronaphthalene as the mobile phase, with a solution concentration of 1.0 mg / mL. After filtration through a 5 μm high-temperature metal filter, the sample was injected. The column temperature was 210°C, and the flow rate was 1.0 mL / min. A calibration curve was established using a calibrated narrow-distribution polymer standard sample of the same type. In this text, Mw and Mn are apparent molecular weights obtained under the same chromatographic conditions and the same calibration curve. The MDC is the ratio of Mw to Mn. The mean and standard deviation of Mw, Mn, and the MDC were recorded, with n ≥ 3.

[0109] Differential scanning calorimetry (DSC) was performed on Examples 1-4 and all comparative examples to evaluate the response of melting point, crystallization temperature, and glass transition temperature to crystal regularity and the degree of introduction of polyethersulfone oligomer segments. The principle was to record the heat flow changes during heating and cooling. The glass transition temperature was determined according to GB / T19466.2-2025, and the melting and crystallization temperatures were determined according to GB / T19466.3-2025. The temperature was increased and decreased at a rate of 10°C / min under a nitrogen atmosphere. The sample mass was 5-8 mg, the nitrogen flow rate was 50 mL / min, and the test procedure was as follows: heating from 30°C to 320°C, holding for 3 min, cooling to 30°C, and then heating again to 320°C. The melting point and glass transition temperature were obtained from the second heating curve, and the crystallization temperature of Examples 1-4 was obtained from the cooling curve. The average value and standard deviation of the corresponding parameters were recorded, with n≥3.

[0110] Total chlorine content was determined for Examples 1-4 and all comparative examples; terminal chlorine group content was determined for Examples 1-4; apparent consumption ratio of terminal hydroxyl groups was calculated for Examples 1-4, Comparative Examples 1-8, Comparative Example 10, and Comparative Example 11. Total chlorine was determined using combustion ion chromatography (CIC), IEC 62321-3-2:2020, which is applicable to the CIC screening of fluorine, chlorine, and bromine in polymers. 20-50 mg of dry sample was weighed and burned in oxygen. The absorbent was a hydrogen peroxide-carbonate absorbent. The chloride ion peak area was recorded by ion chromatography and converted to mg / kg based on the elemental mass of chlorine. Terminal chlorine group content was determined by subtracting the free chlorine content from the total chlorine content: the sample was dissolved in α-chloronaphthalene, cooled, and then ethanol was added and filtered. The filtrate was extracted with aqueous phase, and the free chlorine content was determined. The terminal chlorine group content was calculated by subtracting the free chlorine content from the total chlorine content. When the total chlorine content and free chlorine content, expressed as chlorine elemental mass, are both in mg / kg, the terminal chlorine group content is expressed in mmol / g, and its calculation formula is: Terminal chlorine group content = (Total chlorine content - Free chlorine content) × 10 -3 / 35.45. Both the prepolymer and the final product were measured using independent samples from their respective stages. The apparent consumption ratio of terminal hydroxyl groups was calculated using the following formula: Apparent consumption ratio of terminal hydroxyl groups = (n o -n e -n r ) / n o ×100%; where, n o n represents the amount of terminal hydroxyl groups contained in the hydroxyl-terminated polyethersulfone oligomer being fed. e n represents the amount of terminal hydroxyl groups in the polyethersulfone oligomer recovered from the extract after extraction of the final product in N-methylpyrrolidone at 80°C and a liquid-to-solid mass ratio of 20:1 for 4 hours. rThis refers to the amount of detectable terminal hydroxyl groups remaining in the insoluble matter after extraction. The apparent consumption ratio of terminal hydroxyl groups reflects the overall apparent state of the hydroxyl-terminated polyethersulfone oligomer during chain segmentation and post-processing, and is not equivalent to the aryl ether bond formation rate or the terminal chlorine group consumption rate; this indicator is not calculated for Comparative Example 9, which did not contain hydroxyl-terminated polyethersulfone oligomers. Record the mean and standard deviation, n≥3.

[0111] Ash content, moisture content, and residual N-methylpyrrolidone were tested in Examples 1-4, and the ash content and residual N-methylpyrrolidone data listed in Table 1 were recorded for all comparative examples. The purpose was to evaluate the effects of washing, filtration, and drying post-treatment on inorganic and solvent residues. Ash content was determined according to ISO 3451-1:2026 Method A, with an ignition temperature of 550±25℃, and the constant weight criterion was that the difference between two consecutive weighings should not exceed 0.5 mg. Moisture content was determined using the Karl Fischer method, referring to the Karl Fischer titration principle of GB / T 6283-2008, with the sample subjected to 150℃... Heating extraction was performed and the sample was transferred to a Karl Fischer titration cell. The average and standard deviation of the water content were recorded. Residual N-methylpyrrolidone was analyzed using static headspace gas chromatography with reference to ASTM D4526-20. 0.500 g of the final product powder with a particle size less than 500 μm was weighed and placed in a 20 mL headspace vial. After equilibration at 180 °C for 30 min, the sample was injected and detected with a flame ionization detector. The residual N-methylpyrrolidone was quantified using a matrix-matched external standard curve. The results were converted to mg / kg based on the dry weight of the sample, and the mean and standard deviation were recorded, n≥3.

[0112] The melt flow rate was tested in Examples 1-4 and all comparative examples to evaluate the balance between low residual chlorine control and processing fluidity. The principle is to record the melt extrusion mass per unit time under specified temperature and load. Test conditions were established according to GB / T3682.1-2018: test temperature 316℃, load 5kg, preheating for 5min, and sample drying at 120℃ for 4h before testing. The average melt flow rate, standard deviation, and abnormal flow phenomena were recorded, with n≥3.

[0113] The segment retention rates after extraction were tested for Examples 1-4 and all comparative examples except Comparative Example 9; infrared spectroscopy was recorded for Examples 1, 9, 10, and 11. The purpose of recording the segment retention rates after extraction and the infrared spectra was to help evaluate whether the hydroxyl-terminated polyethersulfone oligomer segments were stably retained and to compare the differences between covalent linkage schemes and physical mixing schemes; infrared spectra were recorded at 4000-600 cm⁻¹ according to ASTM E1252-98(2021). -1 Range, using ATR mode, resolution 4cm -1The scan was performed 32 times, and baseline correction was performed after air background subtraction. Extraction was conducted using N-methylpyrrolidone at 80℃ for 4 hours, followed by drying and weighing. The liquid-to-solid mass ratio was 20:1. The extracted solid was dried at 120℃ for 4 hours. After precipitation, the extract was used to determine the mass of extractable polyethersulfone oligomers. The segment retention rate after extraction was calculated as: (Mass of polyethersulfone oligomer segments retained in the final product after extraction / Mass of polyethersulfone oligomer segments in the final product before extraction) × 100%. For Comparative Example 9, which did not contain hydroxyl-terminated polyethersulfone oligomers, this index was not calculated. The average and standard deviation of the segment retention rate were recorded, with n ≥ 3. The segment retention rate after extraction and the apparent consumption ratio of terminal hydroxyl groups are different evaluation indices and do not have a fixed numerical correspondence. Neither is used as a direct measurement of the aryl ether bond formation rate.

[0114] X-ray photoelectron spectroscopy (XPS) was performed on Examples 1, 10, and 11 to evaluate the consumption of terminal chlorine, introduction of oxygen, and removal of inorganic salts, in conjunction with FTIR and post-extraction chain segment retention. The test samples were the final product powder extracted with N-methylpyrrolidone and dried. AlKα radiation was used, with charge correction at C1s 284.8 eV, and the C1s, O1s, S2p, Cl2p, Na1s, and K2p spectral regions were recorded. Example 1 was compared with the unactivated Comparative Example 10 and the post-melt-mixed Comparative Example 11, and changes in the Cl2p peak area, O / S atomic ratio, and Na / K residue were recorded as auxiliary analytical data for end-group reactions and post-processing purification. A single elemental ratio, single peak area, or single FTIR characteristic peak was not used as the sole basis for confirming the formation of new aryl ether bonds.

[0115] The infrared peak area ratio analysis before and after extraction was performed on Examples 1, 10, and 11 to distinguish the relationship between the characteristic peaks of the polyethersulfone oligomer and the stably retained segments after extraction. The peak area ratio was measured at 1320 cm⁻¹. -1 and 1150cm -1 Nearby sulfone-related peaks, 1245 cm⁻¹ -1 The peak areas of the nearby aryl ether bond-related peaks and the characteristic peaks of the polyphenylene sulfide main chain were normalized, and the changes in the peak area ratio before and after extraction were recorded. This peak area ratio, together with the chain segment retention rate after extraction, the content of terminal chlorine groups, and the X-ray photoelectron spectroscopy results, was used to compare the retention stability of polyether sulfone oligomer segments in different samples, and was not used alone as a basis for determining the covalent linkage of aryl ether bonds.

[0116] To verify the synergistic improvement effect of this invention on dichlorophenyl polyphenylene sulfide in terms of chain segment stability, crystal heat resistance, low residual chlorine, and processing fluidity, the chain segment connection and functional group response were first confirmed by infrared spectroscopy. Figure 1 As shown, in the raw FTIR absorbance spectra of Example 1, Comparative Example 10, and Comparative Example 11, at 3440 cm⁻¹... -1Hydroxyl-related absorption can be observed nearby, at 1320 cm⁻¹. -1 and 1150cm -1 Sulfone-related absorption can be observed nearby, at 1245 cm⁻¹. -1 Nearby, aryl ether bond-related absorptions were observed, indicating that samples obtained from different processes could all reflect the functional group characteristics related to hydroxyl-terminated polyethersulfone oligomer segments, polyphenylene sulfide backbone segments, and aryl ether structures in the original spectra. Further, as... Figure 2 As shown, after baseline correction, the peak shapes and intensities of characteristic absorption peaks such as aromatic rings, sulfone groups, and ether bonds are more clearly distinguished, and the interference of background drift on structure determination is effectively reduced. The aforementioned FTIR characteristic peaks are used to characterize the presence of relevant functional groups in the sample and their relative changes before and after extraction. Since polyethersulfone oligomers themselves contain sulfone groups and aromatic ether bonds, these characteristic peaks alone are not used to confirm the covalent connection of newly formed aromatic ether bonds. End-group reactions and chain segment connectivity should be comprehensively evaluated in conjunction with the chain segment retention rate after extraction, end-group analysis, and X-ray photoelectron spectroscopy results.

[0117] Based on a comprehensive characterization of the chain segment states, the impact of chain segment introduction on crystal regularity and residual chlorine control is further evaluated through thermal analysis and proportioning control results. For example... Figure 3 As shown, the DSC heating heat flow curve of Example 1 shows a melting peak around 295°C and a glass transition temperature around 88°C, indicating that after introducing hydroxyl-terminated polyethersulfone oligomer segments, the polyphenylene sulfide main chain segment still maintains a high degree of crystalline melting characteristics. The melting peak of Example 4 is located around 279°C, with a glass transition temperature of approximately 118°C, indicating that under the higher dry basis ratio of hydroxyl-terminated polyethersulfone oligomers used in Example 4 and the corresponding process conditions, the molecular chain motion and thermal transition behavior of the material show identifiable differences from Example 1, but the crystalline thermal characteristics of polyphenylene sulfide are not completely destroyed. This demonstrates that the present invention does not simply sacrifice the crystalline regularity of polyphenylene sulfide to achieve a modification effect, but rather, by controlling the segment ratio and reaction conditions, allows the aromatic ether linkage segments to improve the end-group state and processing adaptability while maintaining the heat resistance provided by the polyphenylene sulfide main chain segment. Figure 4 This demonstrates the total chlorine content and melt flow rate of Examples 1-4 under different dry basis ratios of hydroxyl-terminated polyethersulfone oligomers and corresponding process conditions. Combining the test results of Examples 3 and 4 in Table 1, under dry basis ratios of 7.00 wt% and 10.00 wt% and corresponding process conditions, the total chlorine content was 840 mg / kg and 320 mg / kg, respectively, and the melt flow rates were 38.0 g / 10 min and 30.5 g / 10 min, respectively. This indicates that the combined process conditions of the examples can balance residual chlorine control and melt processing fluidity. Figure 4 It is not used to indicate the total chlorine content or melt flow rate, which is determined solely by the dry basis ratio of the feed.

[0118] Figure 5 and Figure 6 These parameters were used to assist in comparing the macroscopic powder morphology, microscopic particle morphology, and elemental surface distribution of the final products of Example 1 and Comparative Example 11. This set of characterizations, along with quantitative detection results such as segment retention rate after extraction, total chlorine content, ash content, residual N-methylpyrrolidone, and melt mass flow rate, were used to evaluate the stability of the modified segments and the effect of post-treatment. They were not used alone to confirm covalent linkage of aryl ether bonds, nor were they considered direct evidence of improved mechanical properties.

[0119] Combining the comprehensive performance data of the examples and comparative examples in Table 1, it can be seen that Examples 1-4 exhibit a reasonable balance between the apparent consumption ratio of terminal hydroxyl groups, the retention rate of chain segments after extraction, the total chlorine content, ash content, residual N-methylpyrrolidone, and the melt mass flow rate, indicating that the modified chain segments of the present invention have high retention stability under the specified extraction evaluation conditions. In conventional single-factor comparative examples, deviations in raw material ratio, dehydration water content, polymerization temperature, chain segment connection temperature, or hydrochloric acid washing conditions often lead to a deterioration in at least one of the following indicators: total chlorine content, ash content, residual solvent, thermal behavior, or melt flowability. This indicates that any process parameter deviating from the matching range may disrupt the balance between chain segment stability, heat resistance, low residue, and flowability. Comparative Examples 10 and 11, after not activating terminal hydroxyl groups and changing the chain segment connection sequence, showed lower retention rates and apparent consumption ratios of terminal hydroxyl groups after extraction compared to Example 1, respectively. Comparative Example 9 did not introduce hydroxyl-terminated polyethersulfone oligomers, therefore, the apparent consumption ratio of terminal hydroxyl groups and the retention rate of chain segments after extraction were not calculated.

[0120] In conclusion, Figures 1 to 6 Table 1 provides a comprehensive evaluation from multiple levels, including functional group response, thermal transition behavior, feed ratio window, macroscopic morphology, microscopic morphology, elemental distribution, and overall performance. This invention maintains the crystalline and heat-resistant foundation of the polyphenylene sulfide main chain while enabling hydroxyl-terminated polyethersulfone oligomer segments to stably participate in chain segmentation via aryl ether bonds. Furthermore, it reduces the impact of terminal chlorine and inorganic residues on processing stability through ratio matching, end-group reactions, and post-treatment control. The aforementioned evaluation does not rely solely on a single spectral peak position, a single morphological image, or a single comprehensive index.

[0121] Table 1 Performance of Examples and Comparative Examples Example 1 30.0±1.1 86.2±1.4 295.0±0.9 88.0±0.7 1500±45 0.150±0.006 1000±35 62.0±2.5 Example 2 95.0±1.5 96.8±1.0 275.0±0.8 125.0±1.0 200±12 0.005±0.001 20±3 18.5±1.1 Example 3 62.0±1.2 92.1±1.1 286.0±0.8 106.0±0.8 840±30 0.060±0.004 420±18 38.0±1.6 Example 4 80.0±1.4 95.0±0.9 279.0±0.7 118.0±0.9 320±18 0.020±0.002 80±6 30.5±1.3 Comparative Example 1 22.0±1.0 75.0±1.8 292.0±1.1 92.0±0.9 1420±50 0.160±0.008 980±40 58.0±2.6 Comparative Example 2 25.0±1.2 78.0±1.6 294.0±1.0 89.0±0.8 1520±55 0.145±0.007 990±42 61.0±2.7 Comparative Example 3 33.0±1.4 85.0±1.5 294.0±1.0 88.0±0.8 2100±70 0.152±0.008 980±38 64.0±2.8 Comparative Example 4 28.0±1.3 80.0±1.7 289.0±1.2 87.0±0.9 1850±65 0.220±0.010 1050±45 70.0±3.1 Comparative Example 5 26.0±1.2 79.0±1.7 274.0±1.2 85.0±0.8 1660±60 0.180±0.009 960±40 75.0±3.0 Comparative Example 6 16.0±0.9 68.0±2.0 295.0±1.1 88.0±0.7 1720±60 0.150±0.007 1000±35 66.0±2.9 Comparative Example 7 40.0±1.6 82.0±1.8 265.0±1.5 90.0±1.1 1250±48 0.170±0.009 800±32 15.0±1.0 Comparative Example 8 30.0±1.2 84.0±1.5 294.0±1.0 88.0±0.8 1600±55 0.300±0.012 1100±48 60.0±2.5 Comparative Example 9 not applicable not applicable 296.0±1.0 86.0±0.7 1650±58 0.140±0.007 940±38 72.0±3.0 Comparative Example 10 8.0±0.8 55.0±2.2 284.0±1.2 102.0±0.9 1550±54 0.140±0.007 900±36 55.0±2.4 Comparative Example 11 12.0±0.9 58.0±2.1 286.0±1.1 100.0±0.9 1580±56 0.138±0.007 930±37 57.0±2.5

[0122] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention and not to limit it. Although the present invention has been described in detail with reference to the above embodiments, those skilled in the art should understand that any equivalent structural transformations made under the concept of the present invention and using the contents of the specification and drawings of the present invention should be covered within the scope of protection of the claims of the present invention.

Claims

1. A p-dichlorophenyl polyphenylene sulfide, characterized in that, The p-dichlorophenyl polyphenyl sulfide comprises: The polyphenylene sulfide backbone segment formed by the condensation polymerization of p-dichlorobenzene and sodium sulfide nonahydrate and present in the final product; and The polyethersulfone oligomer segment introduced into and present in the final product is a hydroxyl-terminated polyethersulfone oligomer formed by the polycondensation of 4,4'-dihydroxydiphenyl sulfone and 4,4'-dichlorodiphenyl sulfone. Wherein, the covalent bond between the polyphenylene sulfide main chain segment and the polyethersulfone oligomer chain segment is an aryl ether bond. In the chain linking step of preparing the p-dichlorophenyl polyphenylene sulfide, based on the sum of the dry basis mass of the p-chlorophenyl-terminated polyphenylene sulfide prepolymer used to form the polyphenylene sulfide main chain segment and the hydroxyl-terminated polyethersulfone oligomer used to form the polyethersulfone oligomer chain segment being 100wt%, the dry basis mass of the p-chlorophenyl-terminated polyphenylene sulfide prepolymer is 88.00-98.00wt%, the dry basis mass of the hydroxyl-terminated polyethersulfone oligomer is 2.00-12.00wt%, and the sum of the two is 100wt%.

2. The p-dichlorophenyl polyphenylene sulfide according to claim 1, characterized in that, The total chlorine content of the p-dichlorophenyl polyphenylene sulfide is 200-1500 mg / kg, the ash content is 0.005-0.150 wt%, and the weight-average molecular weight is 2.0 × 10⁻⁶. 4 -8.0×10 4 g / mol; wherein, the total chlorine content, ash content and weight-average molecular weight are all measured using the dried final product as the test sample, the total chlorine content is the total chlorine content of the dried final product as determined by combustion ion chromatography, including covalent chlorine corresponding to the terminal chlorine groups and extractable free chlorine; the value of the terminal chlorine group content converted to chlorine mass is not greater than the total chlorine content.

3. The p-dichlorophenyl polyphenylene sulfide according to claim 1, characterized in that, The polyethersulfone oligomer segments are introduced by hydroxyl-terminated polyethersulfone oligomers, which are prepared by the following steps: A1. Add 4,4'-dihydroxydiphenyl sulfone, 4,4'-dichlorodiphenyl sulfone, anhydrous potassium carbonate, N-methylpyrrolidone, and toluene to a reaction vessel equipped with a stirrer, condenser, and water separator, wherein the molar ratio of 4,4'-dihydroxydiphenyl sulfone to 4,4'-dichlorodiphenyl sulfone is 1.04-1.20:1, and the molar ratio of anhydrous potassium carbonate to 4,4'-dihydroxydiphenyl sulfone is 1.05-1.40:1; A2. Under industrial-grade nitrogen protection, reflux azeotropic dehydration at 140-165℃ for 1.0-3.0h; A3. Heat to 170-190℃ for condensation for 2.0-6.0 h to obtain a reaction solution containing hydroxyl-terminated polyethersulfone oligomers; A4. The reaction solution containing the hydroxyl-terminated polyethersulfone oligomer is subjected to precipitation, washing, filtration and drying to obtain the hydroxyl-terminated polyethersulfone oligomer; The hydroxyl-terminated polyethersulfone oligomer has a number-average molecular weight of 1400-7500 g / mol, a hydroxyl value of 15-80 mg KOH / g, a terminal hydroxyl content of 0.27-1.43 mmol / g, and a residual potassium ion content of 20-1000 mg / kg.

4. The p-dichlorophenyl polyphenylene sulfide according to claim 1, characterized in that, The polyphenylene sulfide backbone segment is introduced by a p-chlorophenyl-terminated polyphenylene sulfide prepolymer, which is prepared by the following steps: B1. In a closed, pressure-resistant reactor equipped with a condenser and water separation unit and under industrial-grade nitrogen protection, sodium sulfide nonahydrate, N-methylpyrrolidone, anhydrous lithium chloride, and anhydrous sodium acetate are added to the reactor, and the temperature is raised to 160-205℃ for dehydration for 1.0-4.0 hours. B2. Add p-dichlorobenzene, wherein the molar ratio of p-dichlorobenzene to sodium sulfide (calculated as anhydrous sodium sulfide) is 1.005-1.050:1; B3. Prepolymerize at 220-245℃ and under system autogenous pressure for 0.5-2.0h, then polymerize at 250-275℃ and under system autogenous pressure for 1.0-4.0h. After solid-liquid separation, washing and drying, the p-chlorophenyl-terminated polyphenylene sulfide prepolymer is obtained. The p-chlorophenyl-terminated polyphenylene sulfide prepolymer has a terminal chlorine group content of 0.020-0.180 mmol / g and a weight-average molecular weight of 1.0 × 10⁻⁶. 4 -6.0×10 4 g / mol, ash content 0.020-0.300wt%.

5. The p-dichlorophenyl polyphenylene sulfide according to claim 4, characterized in that, The polyethersulfone oligomer segments are introduced by a polyethersulfone potassium salt activating solution for forming the covalent linkages of the aromatic ether bonds, the polyethersulfone potassium salt activating solution being prepared by the following steps: C1. The hydroxyl-terminated polyethersulfone oligomer used to introduce the polyethersulfone oligomer segments is added to N-methylpyrrolidone to prepare a hydroxyl-terminated polyethersulfone oligomer solution with a solid content of 5.00-30.00 wt% based on the dry basis mass of the hydroxyl-terminated polyethersulfone oligomer as a percentage of the total mass of the solution. C2. Add anhydrous potassium carbonate to the hydroxyl-terminated polyethersulfone oligomer solution, wherein the molar ratio of anhydrous potassium carbonate to the terminal hydroxyl groups of the hydroxyl-terminated polyethersulfone oligomer is 0.80-2.00:1; C3. Under industrial-grade nitrogen protection, the polyethersulfone potassium salt activation solution is activated at 120-160℃ for 0.5-2.0h to obtain the activated solution. The water content of the polyethersulfone potassium salt activating solution is 20-500 mg / kg, the solid content based on the dry basis mass of the hydroxyl-terminated polyethersulfone oligomer as a percentage of the total mass of the activating solution is 5.00-30.00 wt%, and the undissolved matter is 0-0.50 wt%.

6. The p-dichlorophenyl polyphenylene sulfide according to claim 1, characterized in that, The p-dichlorophenyl polyphenylene sulfide has a terminal chlorine group content of 0.005-0.040 mmol / g, a molecular weight distribution coefficient of 1.8-4.5, and a water content of 0.005-0.100 wt%.

7. The p-dichlorophenyl polyphenylene sulfide according to claim 1, characterized in that, The p-dichlorophenyl polyphenylene sulfide has a melting point of 275-295℃, a crystallization temperature of 210-250℃, and a glass transition temperature of 88-125℃.

8. The p-dichlorophenyl polyphenylene sulfide according to claim 3, characterized in that, The apparent consumption ratio of the terminal hydroxyl groups is 30.00-95.00 mol%, and the apparent consumption ratio of the terminal hydroxyl groups is calculated according to the following formula: Apparent consumption ratio of terminal hydroxyl groups = (n o -n e -n r ) / n o ×100%; Where, n o n represents the amount of terminal hydroxyl groups contained in the hydroxyl-terminated polyethersulfone oligomer being fed. e n represents the amount of terminal hydroxyl groups in the polyethersulfone oligomer recovered from the extract after extraction of the final product in N-methylpyrrolidone at 80°C and a liquid-to-solid mass ratio of 20:1 for 4 hours. r This represents the amount of detectable terminal hydroxyl groups remaining in the insoluble matter after extraction.

9. A method for preparing p-dichlorophenyl polyphenylene sulfide as described in any one of claims 1-8, characterized in that, Includes the following steps: S1. Provides hydroxyl-terminated polyethersulfone oligomers; S2. Sodium sulfide nonahydrate, N-methylpyrrolidone, anhydrous lithium chloride, and anhydrous sodium acetate are added to a sealed pressure-resistant reactor equipped with a condenser and water separator. The mixture is dehydrated at 160-205℃ for 1.0-4.0 h under industrial-grade nitrogen protection. The dehydrated water is discharged after condensation and water separation to obtain a dehydrated sodium sulfide reaction system. The water content of the dehydrated system is 1.00-1.35 mol water / mol sodium sulfide. All amounts of substances related to sodium sulfide in this claim are calculated based on the amount of sodium sulfide nonahydrate converted to anhydrous sodium sulfide. S3. Add p-dichlorobenzene to the dehydrated sodium sulfide reaction system, wherein the molar ratio of p-dichlorobenzene to sodium sulfide is 1.005-1.050:1, react at 220-245℃ and under autogenous pressure for 0.5-2.0 h, then raise the temperature to 250-275℃ and react at autogenous pressure for 1.0-4.0 h, and obtain p-chlorophenyl-terminated polyphenylene sulfide prepolymer after solid-liquid separation, washing and drying; S4. The hydroxyl-terminated polyethersulfone oligomer is added to N-methylpyrrolidone to prepare a hydroxyl-terminated polyethersulfone oligomer solution with a solid content of 5.00-30.00 wt% based on the dry basis mass of the hydroxyl-terminated polyethersulfone oligomer as a percentage of the total mass of the solution. Anhydrous potassium carbonate is added to the hydroxyl-terminated polyethersulfone oligomer solution and activated at 120-160°C under industrial-grade nitrogen protection for 0.5-2.0 h to obtain a polyethersulfone potassium salt activated solution; then, the p-chlorophenyl-terminated polyphenylene sulfide pre- The polyethersulfone potassium salt activating solution is added to the polymer, wherein the amount of the hydroxyl-terminated polyethersulfone oligomer added is 2.04-13.64 wt% of the dry basis mass of the p-chlorophenyl-terminated polyphenylene sulfide prepolymer, and the molar ratio of anhydrous potassium carbonate to the terminal hydroxyl groups of the hydroxyl-terminated polyethersulfone oligomer is 0.80-2.00:

1. Under industrial-grade nitrogen protection, the reaction is carried out at 260-285℃ and autogenous pressure for 0.5-3.0 h to obtain a reaction product with covalent linkage of aryl ether bonds. S5. The reaction product with covalent linkage of aromatic ether bonds is washed, filtered and dried to obtain the p-dichlorophenyl polyphenyl sulfide.

10. The preparation method according to claim 9, characterized in that, In step S2, the molar ratio of sodium sulfide nonahydrate, N-methylpyrrolidone, anhydrous lithium chloride, and anhydrous sodium acetate is 1:3.0-6.5:0.05-0.60:0.05-0.60.

Citation Information

Patent Citations

  • Method for preparing linear high molecular weight polyphenylene sulfide by utilizing pre-desalting method

    CN103275320A

  • A method for preparing polyphenylene sulfide by polycondensation of dichlorobenzene

    CN107254047B